Fate of Organic Carbon Burial in Modern Sediment Within Yangtze River Estuary. Issue 2 (20th February 2020) - Sun, Xueshi; Fan, Dejiang; Liao, Huijie; Tian, Yuan
Abstract: Large river‐dominated margins play a potential key role in regulating global carbon cycle and budget due to high terrestrial organic carbon (Corg ) inputs and sediment accumulation rates. Here bulk elements (Corg and TN), isotopic compositions (δ 13 Corg and δ 15 N), radioisotope 210 Pb, sedimentary grain size, pH, Eh, and physicochemical properties were analyzed on samples from the Yangtze River Estuary to determine the mechanism involved in transporting sedimentary Corg offshore. In addition, nine box‐cores were analyzed to further reveal the potential effects of the declining sediment load on the modern depositional pattern of Corg . The statistical analyses indicate that the hydrodynamically driven sediment composition exerts a significant control on the transport, mobilization, and accumulation of sedimentary Corg from the river to the estuary, with respect to the redistribution of fine‐grained sediments. Furthermore, X‐radiographs and 210 Pb indicate that reworked environment dominates carbon burial in the Yangtze proximal deposit, while a stable sedimentary environment of Corg (3.50–5.58 g cm −2 year −1 ) is observed in the Yangtze distal mud. Notably, the enhanced erosional inputs that contain terrestrial plant debris (mainly the coarse fractions) have tended to become important sources for Corg . Although reworked sediments in the Yangtze River Estuary are frequently exposed to oxygen during physical and biological processes, there appears to be a high potential for long‐term sedimentary Corg storage, due to its association with sediment particles (mainly the clay fractions) that provide physical protection against its degradation. Plain Language Summary: River‐dominated continental margins contribute extensively to burying global Corg within sediments. To elucidate the fate of Corg deposited in estuarine sediments, this study explores how the concentration and composition of sedimentary Corg changes from the river to the estuary and evaluates modern depositional patterns of Corg burial in the Yangtze River Estuary, as suspended sediment and associated terrestrial Corg fluxes from the Yangtze River have decreased 60–80% between 1950 and 2016. Results show that hydrodynamically driven changes to sediment texture primarily dominate the redistribution of sedimentary Corg from the river channel to the estuary. In addition, it is likely that inputs of eroded material that contain terrestrial plant detritus have changed the modern depositional patterns and rates of sedimentary Corg burial in the Yangtze River Estuary. Such changes will inevitably continue to have an impacts on the long‐term burial and preservation of Corg . Key Points: Hydrodynamically driven sediment texture exerts a significant control on the transport and burial of sedimentary Corg Decreased terrigenous sediment load has changed modern deposition patterns and accumulate rates of Corg burial Physical protection of sediment particles likely regulates preservation of sedimentary Corg in this high‐dynamic environment